2019
DOI: 10.1101/gr.243345.118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a primitive intestinal transcription factor network shared between esophageal adenocarcinoma and its precancerous precursor state

Abstract: Esophageal adenocarcinoma (EAC) is one of the most frequent causes of cancer death, and yet compared to other common cancers, we know relatively little about the molecular composition of this tumor type. To further our understanding of this cancer, we have used open chromatin profiling to decipher the transcriptional regulatory networks that are operational in EAC. We have uncovered a transcription factor network that is usually found in primitive intestinal cells during embryonic development, centered on HNF4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 56 publications
8
104
0
Order By: Relevance
“…Supplementary File 5). These peaks are highly enriched in the KLF5 motif, demonstrating the validity of the dataset, and also in AP1(FRA1) and GATA (GATA6) motifs, which we have previously revealed in genome wide studies as implicated in OAC (Britton et al, 2017;Rogerson et al, 2019) (Figure 3-figure supplement 2D). Focussing on the 97 genes that are upregulated in OAC and also downregulated after KLF5 depletion, 97% have a KLF5 ChIPseq peak within 0.5 Mb of the TSS and the median distance between a KLF5 ChIP-seq peak and the TSS of all significantly downregulated genes was 11,975 bp ( Figure 3-figure supplement 2E).…”
Section: Klf5 Controls Expression Of Cell Cycle Genes In Oacsupporting
confidence: 76%
“…Supplementary File 5). These peaks are highly enriched in the KLF5 motif, demonstrating the validity of the dataset, and also in AP1(FRA1) and GATA (GATA6) motifs, which we have previously revealed in genome wide studies as implicated in OAC (Britton et al, 2017;Rogerson et al, 2019) (Figure 3-figure supplement 2D). Focussing on the 97 genes that are upregulated in OAC and also downregulated after KLF5 depletion, 97% have a KLF5 ChIPseq peak within 0.5 Mb of the TSS and the median distance between a KLF5 ChIP-seq peak and the TSS of all significantly downregulated genes was 11,975 bp ( Figure 3-figure supplement 2E).…”
Section: Klf5 Controls Expression Of Cell Cycle Genes In Oacsupporting
confidence: 76%
“…For example, HNF4A is a tumor suppressor in hepatocellular cancer (64) while it was required for maintaining the proliferation of STAD cells (10,42,43). During the preparation of the manuscript, another study was published suggesting that HNF4A-mediated transcriptional program was more active in both Barrett's esophagus and EAC cells than normal esophageal squamous cells (65). Using analysis from unbiased shRNA library screen of over 500 cancer cell lines, we showed that HNF4A is uniquely and specifically essential for the viability of GIAC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In line with its expression being increased in GIAC, inhibition of HNF4A signaling suppressed the growth of GIAC cancer cells and xenografts [ 153 , 183 ]. Conversely, overexpression of HNF4A in adult mouse esophageal explants induced a columnar-like expression profile [ 184 ] and HNF4A alone was sufficient to drive chromatin opening and activation of a esophageal adenocarcinoma-like chromatin signature when expressed in normal human epithelial cells [ 185 ], suggestive of a key role for HNF4A in promoting GIAC initiation and progression. Hence, while the tumor suppressive functions of HNF4A are evident in liver and are in accordance with its role in the maintenance of hepatocellular identity and quiescence, the increased HNF4A expression and tumor promoting actions in GIAC might suggest that, in certain types of cancer, the typical activities of HNF4A as gatekeeper of cell identity are re-rooted towards other functions which, on the contrary, support tumorigenesis.…”
Section: Hnf4 Loss Contributes To Loss Of Identity In Diseasementioning
confidence: 99%